Integrated airborne investigation of the air composition over the Russian sector of the Arctic - B. D. Belan; G. Ancellet; I. S. Andreeva; P. N. Antokhin; V. G. Arshinova; M. Y. Arshinov; Y. S. Balin; V. E. Barsuk; S. B. Belan; D. G. Chernov; D. K. Davydov; A. V. Fofonov; et al. (Atmospheric Measurement Techniques, 2022)
The change of the global climate is most pronounced in the Arctic, where the air temperature increases 2 to 3 times faster than the global average. This process is associated with an increase in the concentration of greenhouse gases in the atmosphere. There are publications predicting the sharp increase in methane emissions into the atmosphere due to permafrost thawing. Therefore, it is important to study how the air composition in the Arctic changes in the changing climate. In the Russian sector of the Arctic, the air composition was measured only in the surface atmospheric layer at the coastal stations or earlier at the drifting stations. Vertical distributions of gas constituents of the atmosphere and aerosol were determined only in a few small regions. That is why the integrated experiment was carried out to measure the composition of the troposphere in the entire Russian sector of the Arctic from on board the Optik Tu-134 aircraft laboratory in the period of 4 to 17 September of 2020. The aircraft laboratory was equipped with contact and remote measurement facilities. The contact facilities were capable of measuring the concentrations of CO 2 , CH 4 , O 3 , CO, NO x , and SO 2 , as well as the disperse composition of particles in the size range from 3 nm to 32 µ m, black carbon, and organic and inorganic components of atmospheric aerosol. The remote facilities were operated to measure the water transparency in the upper layer of the ocean, the chlorophyll content in water, and spectral characteristics of the underlying surface. The measured data have shown that the ocean continues absorbing CO 2 . This process is most intense over the Barents and Kara seas. The recorded methane concentration was increased over all the Arctic seas, reaching 2090 ppb in the near-water layer over the Kara Sea. The contents of other gas components and black carbon were close to the background level. In bioaerosol, bacteria predominated among the identified microorganisms. In most samples, they were represented by coccal forms, ...